Using activity domain theory for managing complex systems - Taxen, Lars, 1944-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2010)
Latest research indicates that construction of a communal meaning regarding coordination of complex systems development tasks should be implemented into practice, proving that far more attention should be given to the issue of communal meaning construction in organizations. This book offers a new approach towards managing complex systems that informs the co-construction of technical support for coordination and communal meaning regarding this support. Compiling and structuring empirical observations from the Ericsson Company and theoretical developments from the perspective of meaning construction, it combines a deep understanding of concrete, everyday conditions of the telecom industry with innovative theoretical development of the Activity Domain Theory (ADT).
The dawn of the activity domain theory -- Reflection -- The philosophical roots -- Activity theory -- The constitution of the activity domain -- Cognitive grounding -- Operationalizing the theory -- Positioning against other theories -- The practical and theoretical trails in hindsight -- The anatomy-centric approach towards managing complex projects -- Enterprise architectures -- Product lifecycle management revisited -- Alignment -- In search of an integrating construct -- In conclusion.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 26, 2010).
Keywords: System theory; Network analysis (Planning); Management information systems; Workflow -- Management; Industrial management; Activity domain; Activity Domain Theory; Activity modalities; Agile development of software; Alignment of business and knowledge strategies; Anatomy-centric approach; Business processes; Cognitive grounding; Common understanding, communal meaning; Complex systems theory; Congruence mind-activity; Coordination; Coordination of the development of the 3rd generation of mobile telecom systems at Ericsson; Cultural-historical Activity Theory; Dialectical method; Enterprise architectures; Information modeling projects; Integration centric development method; IS/IT architectures; Mediation; Mediational means; Practical guiding principles for managing complex systems; Practice-based theories; Praxis; Product life-cycle management; Electronic books